Association of comprehensive correct HIV/AIDS knowledge among caregivers of children living with HIV and disclosure of HIV status - Nishanth Krishna Kodyalamoole; Sanjeev B Badiger (Wolters Kluwer Medknow Publications, 2021)
Context: Knowledge regarding HIV/AIDS results in better self-care and lesser risk behavior. For children living with HIV (CLHIV) since birth, the caregivers need to disclose the HIV status for them to know regarding HIV. Poor knowledge among caregivers is a barrier to the disclosure of HIV status. Aims: The aim is to assess the knowledge among caregivers of CLHIV regarding HIV/AIDS and to evaluate the association between comprehensive correct HIV/AIDS knowledge (CCAK) among caregivers of CLHIV and disclosure of HIV status. Settings and Design: A cross-sectional study was conducted among 91 caregivers of CLHIV in an antiretroviral therapy center in southern coastal Karnataka between October 2014 and July 2015. Subjects and Methods: The data were collected using a structured questionnaire by interview method. Statistical Analysis Used: Frequencies were calculated for the categorical data. For scoring, the correct answers and wrong answer and "Don't know" options were given one mark and zero marks, respectively. Chi-square test was done to check for the association between knowledge and disclosure of the child's HIV status. Results: The knowledge regarding HIV/AIDS was good in 90% of the cases and moderate in the remaining 10%. However, the CCAK was present in only around 40% of the caregivers. The lowest knowledge was regarding the benefits of condom in preventing transmission of HIV. There was no association between CCAK and disclosure of HIV status to the CLHIV in the present study. Conclusions: Although the overall knowledge regarding HIV/AIDS was good among caregivers, they lacked CCAK. There was no association between CCAK and disclosure of the HIV status to the child.